Clinical Presentation and Disease Course of 37 Consecutive Cases of Progressive Multifocal Leukoencephalopathy (PML) at a German Tertiary-Care Hospital: A Retrospective Observational Study - Graf, Lisa M.; Rosenkranz, Sina C.; Hölzemer, Angelique; Hagel, Christian; Goebell, Einar; Jordan, Sabine; Friese, Manuel A.; Addo, Marylyn M.; Schulze zur Wiesch, Julian; Beisel, Claudia (Frontiers in Neurology, 2021)
Background: Progressive multifocal leukoencephalopathy (PML) caused by JCV is a rare but frequently fatal disease of the central nervous system, usually affecting immunocompromised individuals. Our study aims to expand the data on patient characteristics, diagnosis, clinical course, possible PML-directed treatment and outcome of patients with PML at a German tertiary-care hospital. Methods: In this single-center observational cohort study, 37 consecutive patients with a confirmed diagnosis of PML seen at the University Medical Center Hamburg-Eppendorf from 2013 until 2019 were retrospectively analyzed by chart review with a special focus on demographics, risk factors, and clinical aspects as well as PML-directed treatment and survival. Results: We identified 37 patients with definite, probable, and possible PML diagnosis. 36 patients (97%) had underlying immunosuppressive disorders such as HIV/AIDS (n = 17; 46%), previous treatment with monoclonal antibodies (n = 6; 16%), hematological or oncological malignancies (n = 6; 16%), sarcoidosis (n = 5; 14%), solid organ transplantation (n = 1; 3%) and diagnosis of mixed connective tissue disease (n = 1; 3%). In only one patient no evident immunocompromised condition was detected (n = 1; 3%). Treatment attempts to improve the outcome of PML were reported in 13 patients (n = 13; 35%). 27% of patients were lost to follow-up (n = 10). 24-month survival rate after diagnosis of PML was 56% (n = 15). Conclusion: This interdisciplinary retrospective study describes epidemiology, risk factors, clinical course, and treatment trials in patients with PML at a German tertiary-care hospital. Acquired immunosuppression due to HIV-1 constituted the leading cause of PML in this monocenter cohort.